2023
DOI: 10.3389/fcvm.2023.1125063
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune-related hub genes and analysis of infiltrated immune cells of idiopathic pulmonary artery hypertension

Abstract: ObjectivesIdiopathic pulmonary artery hypertension (IPAH) is a rare but life-threaten disease. However, the mechanism underlying IPAH is unclear. In this study, underlying mechanism, infiltration of immune cells, and immune-related hub genes of IPAH were analyzed via bioinformatics.MethodsGSE15197, GSE48149, GSE113439, and GSE117261 were merged as lung dataset. Weighted gene correlation network analysis (WGCNA) was used to construct the co-expression gene networks of IPAH. Gene Ontology and pathway enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Histopathological evidence has suggested that perivascular infiltration of inflammatory cells is common in PH and precedes structural remodelling in vessels [ 5 , 6 , 17 , 21 , 22 ]. In idiopathic PH, the level of immune infiltration is higher for CD8 + T cells, resting memory CD4 + T cells, γδ T cells, M1/M2 macrophages and resting mast cells; and lower for monocytes, neutrophils and naïve CD4 + T cells [ 23 – 25 ]. These results suggest that immune imbalance contributes to remodelling in PH.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological evidence has suggested that perivascular infiltration of inflammatory cells is common in PH and precedes structural remodelling in vessels [ 5 , 6 , 17 , 21 , 22 ]. In idiopathic PH, the level of immune infiltration is higher for CD8 + T cells, resting memory CD4 + T cells, γδ T cells, M1/M2 macrophages and resting mast cells; and lower for monocytes, neutrophils and naïve CD4 + T cells [ 23 – 25 ]. These results suggest that immune imbalance contributes to remodelling in PH.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have used transcriptome sequencing and bioinformatics analysis to screen differentially expressed genes (DEGs) in pulmonary hypertension and further investigate potential biomarkers and regulatory targets. Several transcriptome studies have analyzed the DEGs in cells from patients with idiopathic PH and in the lung tissue of rat models of pulmonary hypertension induced by monocrotaline; these studies have found that DEGs are mainly enriched in the abnormal proliferation of smooth muscle cells and endothelial cells, as well as in inflammatory reactions 5 10 . Another transcriptome study compared 32 mouse strains exposed to chronic hypoxia and found that right ventricular systolic pressure (RVSP) was significantly elevated in the PL/J mouse strain, as well as that the immune inflammatory reaction was the most noticeably enriched 11 .…”
Section: Introductionmentioning
confidence: 99%